OPTIMALISASI ALOKASI ASET DI PASAR MODAL PADA INDUSTRI ASURANSI INDONESIA - Nurdiana Agustina (PRISMAKOM, 2021)
A mathematical formula strategy is needed to minimize investment management errors as the cause of the insurance industry failing to pay claims to customers. By adhering to the investment limits set by the regulator, prudent and optimal investment management must prioritize the allocation of assets to investment instruments with fixed income (money market) and low risk to meet the company’s definite obligations. Then, if there is a residual, it can be allocated to a variable income investment instrument (capital market) which has a high return and high risk to increase the company's income with the simplex method linear programming model. Based on the basic assumptions presented in PT Taspen’s 2020 RKAP (Persero) investment assets can be allocated to investment instruments in the capital market worth Rp. 30,603,568,822,753,- or as much as 29.29% of the total investment can be in the form of stocks with an allocation weight of 14.95 %, mutual funds with an allocation weight of 11.27%, bonds with an allocation weight of 50.0%, medium terms notes with an allocation weight of 5.0%, and KIK-EBA with an allocation weight of 18.79%. So it is expected that the return on investment on December 31, 2020 will reach Rp. 9,900,434,973,836,-.